Educational level-dependent melanoma awareness in a high-risk population in Switzerland - Mueller, Alina Miriam; Goessinger, Elisabeth Victoria; Cerminara, Sara Elisa; Kostner, Lisa; Amaral, Margarida; Huber, Stephanie Marie; Passweg, Lea Pauline; Moreno, Laura Garcia; Bodenmann, Daniel; Kunz, Michael; Levesque, Mitchell Paul; Maul, Julia-Tatjana; et al. (Frontiers in Oncology, 2023)
The worldwide incidence of melanoma has been increasing rapidly in recent decades with Switzerland having one of the highest rates in Europe. Ultraviolet (UV) radiation is one of the main risk factors for skin cancer. Our objective was to investigate UV protective behavior and melanoma awareness in a high-risk cohort for melanoma. In this prospective monocentric study, we assessed general melanoma awareness and UV protection habits in at-risk patients (≥100 nevi, ≥5 dysplastic nevi, known CDKN2A mutation, and/or positive family history) and melanoma patients using questionnaires. Between 01/2021 and 03/2022, a total of 269 patients (53.5% at-risk patients, 46.5% melanoma patients) were included. We observed a significant trend toward using a higher sun protection factor (SPF) in melanoma patients compared with at-risk patients (SPF 50+: 48% [n=60] vs. 26% [n=37]; p=0.0016). Those with a college or university degree used a high SPF significantly more often than patients with lower education levels (p=0.0007). However, higher educational levels correlated with increased annual sun exposure (p=0.041). Neither a positive family history for melanoma, nor gender or Fitzpatrick skin type influenced sun protection behavior. An age of  50 years presented as a significant risk factor for melanoma development with an odd’s ratio of 2.32. Study participation resulted in improved sun protection behavior with 51% reporting more frequent sunscreen use after study inclusion. UV protection remains a critical factor in melanoma prevention. We suggest that melanoma awareness should continue to be raised though public skin cancer prevention campaigns with a particular focus on individuals with low levels of education.